High-intensity activity in European vs. national Rugby Union Games in the best 2014-2015 team - Fornasier-Santos, C.; Millet, G. P; Stridgeon, P.; Girard, O.; Brocherie, F.; Nottin, S. (International Journal of Sports Medicine, 2021)
The purpose of this study is to evaluate the influence of competition level on running patterns for five playing position in the most successful 2014-2015 European rugby union team. Seventeen French rugby union championship and seven European rugby Champions Cup games were analysed. Global positioning system (sampling: 10 Hz) were used to determine high-speed movements, high-intensity accelerations, repeated high-intensity efforts and high-intensity micro-movements characteristics for five positional groups. During European Champions Cup games, front row forwards performed a higher number of repeated high-intensity efforts compared to National championship games (5.8±1.6 vs. 3.6±2.3; +61.1%), and back row forwards travelled greater distance both at high-speed movements (3.4±1.8 vs. 2.4±0.9 m·min-1; +41.7%) and after high-intensity accelerations (78.2±14.0 vs. 68.1 ±13.4 m; +14.8%). In backs, scrum halves carried out more high-intensity accelerations (24.7±3.1 vs. 14.8±5.0; +66.3%) whereas outside backs completed a higher number of high-speed movements (62.7±25.4 vs. 48.3±17.0; +29.8%) and repeated high-intensity efforts (13.5±4.6 vs. 9.7±4.9; +39.2%). These results highlighted that the competition level affected the high-intensity activity differently among the five playing positions. Consequently, training programs in elite rugby should be tailored taking into account both the level of competition and the high-intensity running pattern of each playing position.